How monetary policy affects industrial activity in Malawi: Evidence from ARDL and VAR models - Joseph Upile Matola (Cogent Economics & Finance, 2023)
In this paper, the impact of monetary policy on industrial production is investigated for Malawi. Using the ARDL bounds testing approach, and VAR models, it is shown that tight monetary conditions negatively affect industrial production both in the short run and in the long run. This is the case whether the central bank's policy rate or reserve money is used as the policy tool. The study further establishes the interest rate channel, and money supply channel as the main mechanisms through which this effect of monetary policy is transmitted to industrial production. Given these results, a recommendation is made that the Reserve Bank of Malawi should refrain from prolonged use of tight monetary policy in their quest to achieve stability of prices as this stifles growth of the industrial sector. Rather monetary policy should be used as a temporary stabilization tool when faced with temporary shocks to the bank's policy objectives.
Keywords: E52; E60; E50; 330; monetary policy; autoregressive-distributed lag; industrial production; vector autoregression